2012
DOI: 10.1128/aem.07123-11
|View full text |Cite
|
Sign up to set email alerts
|

A 50-Kilodalton Cry2A Peptide Is Lethal to Bombyx mori and Lymantria dispar

Abstract: ABSTRACTThe Cry2Aa3 gene was introduced into asporogenicBacillus thuringiensis, and the synthesized protoxin killedBombyx moriandLymantria disparlarvae. Chymotrypsin hydrolyzed the linkages between 49Tyr/Val50 and 145Lys/Ser146 in the protoxin, and 50- and 58-kDa fragment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…Previously, cleavage of the Cry2Aa1 and Cry2Aa3 protoxins by Lymantria dispar and B. mori larvae midgut juice produced two major bands, 58 and 49 kDa toxins. N-terminal sequencing confirmed that the first cleavage site was at Tyr49, which is on the loop between α-0 and α-1, while the second cleavage site was at Leu144, which is on the loop between α-3 and α-4 [35,36].…”
Section: Discussionmentioning
confidence: 92%
“…Previously, cleavage of the Cry2Aa1 and Cry2Aa3 protoxins by Lymantria dispar and B. mori larvae midgut juice produced two major bands, 58 and 49 kDa toxins. N-terminal sequencing confirmed that the first cleavage site was at Tyr49, which is on the loop between α-0 and α-1, while the second cleavage site was at Leu144, which is on the loop between α-3 and α-4 [35,36].…”
Section: Discussionmentioning
confidence: 92%
“…The polymerase chain reaction (PCR) technique has been widely used for the identification and characterisation of Bt genes, including cry2A ‐type genes . In the present study, the PCR assay was used to identify the Cry content of the Bt strains under investigation using the set (Cry2A, Cry2B) amplifying a region of 570 bp.…”
Section: Resultsmentioning
confidence: 99%
“…The polymerase chain reaction (PCR) technique has been widely used for the identification and characterisation of Bt genes, including cry2A-type genes. 11,16,28,29 In the present study, the PCR assay was used to identify the Cry content of the Bt strains under investigation using the set (Cry2A, Cry2B) amplifying a region of 570 bp. The results revealed that only six (BUPM109, BLB30, BLB140, BLB200, BLB240 and MEB4) of the 15 selected strains could harbour the cry2A-type genes.…”
Section: Identification Of Cry2a-type Genesmentioning
confidence: 99%
See 2 more Smart Citations